Pneumocystis jirovecii pneumonia in HIV-negative patients, a frequently overlooked problem. A case series from a large Italian center - Giorgio Bozzi; Paola Saltini; Malvina Matera; Valentina Morena; Valeria Castelli; Anna Maria Peri; Lucia Taramasso; Riccardo Ungaro; Andrea Lombardi; Antonio Muscatello; Patrizia Bono; Anna Grancini; et al. (International Journal of Infectious Diseases, 2022)
Background and objectives: Pneumocystis jirovecii pneumonia (PCP) still has substantial morbidity and mortality. For non-HIV patients, the course of infection is severe, and management guidelines are relatively recent. We collected all PCP cases (European Organization for Research and Treatment of Cancer criteria) diagnosed in HIV-negative adult inpatients in 2019-2020 at our center in northern Italy. Results: Of 20 cases, nine had microbiologic evidence of probable (real-time polymerase chain reaction, RT-PCR) and 11 proven (immunofluorescence) PCP on respiratory specimens. Half were female; the median age was 71.5 years; 14 of 20 patients had hematologic malignancies, five had autoimmune/hyperinflammatory disorders, and one had a solid tumor. RT-PCR cycle threshold (Ct) was 24-37 for bronchoalveolar lavage (BAL) and 32-39 for sputum; Ct was 24-33 on BAL proven cases. Of 20 cases, four received additional diagnoses on BAL. At PCP diagnosis, all patients were not on anti-pneumocystis prophylaxis. We retrospectively assessed prophylaxis indications: 9/20 patients had a main indication, 5/9 because of prednisone treatment ≥ 20 mg (or equivalents) for ≥4 weeks. All patients underwent antimicrobial treatment according to guidelines; 18/20 with concomitant corticosteroids. A total of 4/20 patients died within 28 days from diagnosis. Conclusion: Despite appropriate treatment, PCP is still associated to high mortality (20%) among non-HIV patients. Strict adherence to prophylaxis guidelines, awareness of gray areas, and prompt diagnosis can help manage this frequently overlooked infection.